OTORITAS MORAL DALAM CERPEN ARAB JUGHRAFIYĀ : KAJIAN SASTRA BANDINGAN DENGAN CERPEN INDONESIA - Mahirah, Siti Khansa; Nursida, Ida; Rohman, Mohamad (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2026)
This study examines the construction of moral authority in the Arabic short story Jughrafiyā by Faryal Khalifah, with a comparative reference to the Indonesian short story Robohnya Surau Kami by A.A. Navis. This topic is significant as critiques of moral authority in literature reflect the relationship between individual experiences, social values, and collective responsibility within society. Although numerous studies have explored morality in literature, research that specifically investigates the interplay between textual structure, collective consciousness, and socio-historical context in shaping moral authority remains limited. This study aims to fill this gap by employing a qualitative descriptive-analytical method and the perspective of Goldmann’s Genetic Structuralism. The analysis of textual elements, narrative structure, and socio-historical context reveals that the moral authority of the father figure in Jughrafiyā is symbolic and reflective, rooted in historical experience and collective trauma. In contrast, moral legitimacy in Robohnya Surau Kami is primarily ritualistic and detached from social responsibility. These findings highlight that moral authority becomes effective only when manifested in concrete social action, while also contributing to a broader understanding of moral critique in Arabic literature and cross-cultural literary studies.